PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE OPERASI TERHADAP PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI - . CECILIA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Earnings information is a component of the company's financial statements that aim to assess the performance of management, to help estimate the ability of earnings, predicted earnings, assess risks in invest. It is aware of management, so management tends to disfuctional behavior (inappropriate behavior) is to perform income smoothing to resolve conflicts that arise between management and the various stakeholders in the company. Therefore, this study aims to examine the effect of firm size, profitability, and operating leverage of income smoothing. This quantitative study aimed to examine the factors that influence income smoothing. Independent variables are firm size, profitability, and operating leverage. Firm size is measured by the natural logarithm of total assets, profitability measured by return on assets, and operating leverage is measured by the total cost of amortization and depreciation to the total cost. Object of study is a manufacturing company listed on the Indonesia Stock Exchange in 2008-2010. Samples used in the study by 67 manufacturing companies selected by purposive sampling technique. Sources of data obtained from the Indonesian Capital Market Directory. Techniques of data analysis using logistic regression.The analysis shows that firm size and leverage does not affect the operation of income smoothing, while profitability, smoothing effect on income.